PREVALENCE STUDY OF CLINICAL INDICATIONS FOR BREAST MRI - Oliveira, Ilse Franco de; Diniz, Camila Leal; Rahal, Rosemar Macedo de Souza; Gonçalves, Macks Wendhell; Ruiz, Cristina Pinto Naldi; Lauar, Marcelo Vilela; Almeida, Paulinelly Messias de; Freitas-Junior, Ruffo (Mastology, 2026)
Objective: This is a cross-sectional study of the clinical indications and prevalence of breast magnetic resonance scan. Methods: Data were collected retrospectively from women who had breast MRI performed at the Clínica São Marcelo and who agreed to participate in the study during the period 2020–2021. The data were extracted from the anamneses and respective medical reports of 308 women who had breast MRI scans and analyzed using the SPSS statistical software version 26.0. Results: The predominant age group was 40–49 years with a relative frequency of 34.9%, followed by 50–59 years representing 26.7%, women over 60 years with a frequency of 19.9% and 18–39 years with a relative frequency of 18.6%. Regarding clinical indications for breast MRI, breast lump presented 28.2% of indications, breast prosthesis control accounted for 11.7%, family history of cancer 11.7%, breast cancer control 9.4%, post-treatment control 8.4%, screening 6.5%, breast cancer follow-up 5.5%, dense breast 5.5%, family history of cancer and nodule 4.9%, preoperative 3.2%, asymmetry 2.3%, microcalcifications 1.3%, and breast cancer mutation 1.0%. In the Bi-Rads classification, higher percentage for Bi-Rads 2 represented 49.8% and Bi-Rads 3 with a frequency of 27%; Bi-Rads 4 represented 13.4%, Bi-Rads 6 with 5.5%, Bi-Rads 1 with 3.3%, and Bi-Rads 5 represented 1.0% of the classifications of the medical reports. Conclusion: This study showed the predominant age group of the women who attended was 40–49 years, and the most prevalent clinical indication for breast MRI was breast lump.